Isovitexin-Mediated Regulation of Microglial Polarization in Lipopolysaccharide-Induced Neuroinflammation via Activation of the CaMKKβ/AMPK-PGC-1α Signaling Axis - Liu, Bingrun; Huang, Bingxu; Hu, Guiqiu; He, Dewei; Li, Yuhang; Ran, Xin; Du, Jian; Fu, Shoupeng; Liu, Dianfeng (Frontiers in Immunology, 2019)
Microglia, proinflammatory M1 and anti-inflammatory M2 phenotypes immune cells in the brain, has the function of phagocytosis of foreign bodies in the central nervous system. Overactivated microglia causes the production of a large number of neurotoxic factors, which cause neuroinflammatory response and then result in brain disorders. Inflammatory response in the brain plays a crucial part in the pathophysiology of many psychiatric and neurological diseases. It has been demonstrated that inhibiting of M1 phenotype and enhancing of M2 phenotype provide an underlying therapeutic tactics for the prevention and treatment of neuroinflammation-mediated brain diseases. Isovitexin (IVX) has been reported to pass through blood-brain barriers and possess anti-inflammatory activity. However, the effect of IVX on microglia polarization and the involved molecular mechanisms remain unclear. In this study, we found that IVX suppressed the gene production of M1 marks and enhanced the gene production of M2 marks in lipopolysaccharide (LPS)-induced microglial cells line BV-2 cells. And we also found that IVX enhanced the gene and protein exprssion of peroxisome proliferator-activated receptor gamma (PPARγ) and PPARγ coactivator-1α (PGC-1α) in LPS-induced BV-2 cells. Western blotting results showed that IVX treatment increased the expression levels of p-CaMKKβ, p-AMPK and PGC-1α in BV-2 cells. Pretreatment with STO-609 (an inhibitor of CaMKKβ) or SR-18292 (an inhibitor of PGC-1α) attenuated the regulating of IVX in microglia M1/ M2 polarization in LPS-induced BV-2 cells. After mouse was treated with STO-609 or SR-18292, the effect of IVX on LPS-injected mouse was measured using behavioral test, RT-PCR and western blot, respectively. Our results showed that the inhibition of CaMKKβ or PGC-1α attenuated the prevention of IVX on sickness behavior and the enhancement of IVX on microglia M2 phenotype in LPS-injected mouse. Overall, we found that IVX regulated microglia M1/M2 polarization in LPS-induced neuroinflammation via activation of CaMKKβ/AMPK-PGC-1α signaling axis.